A new species of Rhytidognathus (Carabidae, Migadopini) from Argentina - Roig, Sergio Alberto (2012)
The Migadopini are a small tribe of Carabidae with 47 species that occur in South America, Australia, and New Zealand, in the sub-Antarctic areas. In South America, most of the genera inhabit areas related to sub-Antartic Nothofagus forest except two monogeneric genera, the Ecuadorian genus Aquilex Moret and the Pampean genus Rhytidognathus Chaudoir. These two genera are geographically isolated from the remaining five South American genera. New material of Rhytidognathus from the northeast of Buenos Aires province and from Entre Ríos province permits establishing that the previous records of Rhytidognathus ovalis (Dejean) for Argentina were erroneous and that it belongs to a new species. Based on external morphological characters and from male and female genitalia we describe Rhytidognathus platensis as a new species. In this contribution we provide illustrations, keys, habitat characteristics and some biogeographic considerations on the distribution of Rhytidognathus.